Wpływ integracji europejskiej na przemiany społeczne i kulturowe obszarów wiejskich - Woźniak, Marian; Cyrek, Magdalena (Influence of European Integration on Social and Cultural Changes of Rural Areas, 2005)
Basic conditions of socio-cultural changes of rural areas ensuing from European integration processes are presented in the study. A role of support for restructuring within rural policy as well as a meaning of economic factors in the sphere of incomes and employment are stressed. Special attention is drawn to an aspect of multifunctional development of rural areas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 423-428